“In Flanders Fields” — Canada’s Official Poem:: Breaking Faith - Holmes, Nancy (Studies in Canadian Literature / Études en littérature canadienne, 2005)
John McCrae's "In Flanders Fields" now appears on the ten-dollar bill, its place firmly established within Canadian iconography. Yet the poem has been dismissed by both critics and poets as blithely Romantic and/or jingoistic, yet a close reading of the text reveals a deeper, conflicted significance. In the first two stanzas, McCrae uses conventional pastoral imagery to disrupt the familiar association between Christian ideals of redemption and renewal with nature, hauntingly capturing the uncertainty and fear that pervaded the collective consciousness of soldiers and civilians alike, both during and after World War I. However, in the last stanza, McCrae abandons his skillful representation of the war torn, spiritually diseased soul by applying an ideological gloss that reads like a recruiting poster. The critical silence surrounding the complexities of this poem have led to its reappropriation by the Canadian government as a symbol of the military and heroism rather than a rite of genuine war remembrance.